Peningkatan Keberanian Berbicara Siswa melalui Game Edukatif The Shield of Faith - Nanda Yustina; Dian Arlianty (Advances In Education Journal, 2025)
The educational game The Shield of Faith is presented as an instructional innovation designed to cultivate students’ capacity to articulate their opinions in an assertive, logical, and decorous manner. Conceptualized as an interactive simulation integrating role-play and structured discussion, the game engages students in the active construction of ideas, critical examination of contextual issues, and the development of consistent communicative practices. Employing an experiential learning framework combined with group psychoeducation, the program is systematically structured to enhance cognitive domains (including the identification of potential culture shock and moral challenges), affective domains (such as the adoption of appropriate attitudes and sound decision-making), and psychomotor domains (notably the ability to formulate firm yet courteous refusal strategies). This community engagement initiative aims to reinforce the verbal communication competencies of senior high school students at Dayah Terpadu Al Muslimun Lhoksukon, Aceh Utara. Evaluation outcomes demonstrate a substantial improvement in students’ willingness and confidence to express their viewpoints, as reflected in increased verbal participation, elevated argumentative quality, and more active involvement in collaborative discussions.